PELAKSANAAN GADAI DAN CICIL EMAS DI BANK SYARIAH INDONESIA KCP MALANG KEPANJEN 1 DALAM PERSPEKTIF PERBANKAN SYARIAH - Reka Indriani; Muhammad Alhada Fuadillah Habib (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The merger of the three Islamic banks aims to create the largest Islamic bank in Indonesia through unification of core capital in its operational activities. The financing products offered by Indonesian Islamic banks themselves also vary according to the needs of the community, one of the products that are in great demand by the public is gold mortgage products and gold installments. Basically, an Islamic bank is a business entity that must be implemented according to sharia principles. However, in its implementation in the field, there are still several Islamic bank institutions that have not implemented sharia principles in carrying out their business. For this reason, this study aims to analyze how the process of implementing gold pawning and gold installments at Bank Syariah Indonesia KCP Malang Kepanjen 1 in the perspective of Islamic banking. The method used in this study is a qualitative descriptive method in which data are obtained from interviews, observations, and literature studies. Based on the research that has been done, the results show that the process of implementing gold pawning and gold installments at Bank Syariah Indonesia KCP Malang Kepanjen 1 is in accordance with the perspective of Islamic banking, it is proven that in the process of carrying out its activities it has implemented contracts that are in accordance with sharia provisions and in accordance with the principles - sharia economic principles, namely sharia banking must be based on the principle of being free from acts of maysir, gharar and usury, apply the principles (fairness, partnership, transparency, and universals), apply the principles of trust and prudence in managing its operational activities, and use a contract that in accordance with Islamic law that has been taught Rasulullah SAW.